Variability of coconut phenotype based on morphology and content of fatty acids in Asahan District, North Sumatra, Indonesia - Luthfi Aziz Mahmud Siregar; Risma Damayanti; Diana Sofia Hanafiah (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Siregar LAM, Damayanti R, Hanafiah DS. 2019. Variability of coconut phenotype based on morphology and content of fatty acids in Asahan District, North Sumatra, Indonesia. Biodiversitas 20: 3413-3421. A study that aims to determine the diversity, relationship and fatty acid content in several coconut genotypes (Cocos nucifera L.) grown and cultivated in Asahan District of North Sumatra Province, Indonesia was investigated. The coconut was obtained from the Air Joman and Silau Laut subdistricts of Asahan District, between April and September 2017. This study used morphological observation method based on IPGRI (International Plant Genetic Resources Institute) coconut descriptor with purposive sampling technique. A total of 36 coconut genotypes have been collected and identified based on morphological characters and fatty acid content. Based on the morphological character, the genotype of G28 and G32 show the closest relationship with the dissimilarity value of 3.00 and the farthest relationship on the genotype of G40 and G43 with the dissimilarity value of 12.04. Based on the 10 main type fatty acids found in coconut oil, all genotypes have between 8 and 10 types of fatty acids, i.e. caprylic, capric, myristic, palmitic, stearic, oleic, linoleic and arachidic acid in the oil. The average amount of fatty acid contained in coconut oil obtained generally in other coconut oil. Genotype of G5 has the highest content of lauric acid and has 12.1 mm thick flesh, but only 8 types of fatty acid composition are present in the oil.